Raoul Hausmann ou la subversion des identités nationales - Hélène Thiérard (Recherches Germaniques)
This article examines the German-French literary production of Raoul Hausmann, in particular after his exile of 1933. Having fled Nazi Germany, the former Berlin Dadaist found refuge in France where he lived until his death in 1971. Making French his second writing language, the former Berlin Dadaist adopted from 1945 onwards a strategy of bilingual writing keeping his two languages separate from book to book, in an attempt to gain recognition as a German writer and a French writer in parallel. While this divided authorship follows the logic of national literatures, at the same time Hausmann developed a plurilingual poetics in major works such as Hyle II or PIN, which vehemently opposed the ideology of national identities and their supposed cultural homogeneity. The analysis of Hyle, Ein Traumsein in Spanien, which Hausmann worked on from 1933 to 1958, illuminates the tension between these two practices of plurilingualism after 1945.